PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS SAINTIFIK TEMA 6 PANAS DAN PERPINDAHANNYA UNTUK KELAS V SDN 36 GUNUNG SARIK KOTA PADANG - Dwintan Sefrida; Enjoni Enjoni (Program Studi PGSD FKIP Universitas Bung Hatta, 2022)
ABSTRACT This study aims to produce scientific-based science learning Modules for fifth grade students at SDN 36 Gunung Sarik, Padang City, which meet the valid, practical and effectve criteria. This type of research is research and development (Research and Development). Based on the theory proposed by Sugiyono (2013), the development research model used is 4-D, namely define, design, develop, and disseminate. Due to time constraints, the research only reached the development phase (3-D). The research instrument includes a validation sheet which is validated by 3 lecturers and a practical sheet for 1 educator and 26 fifth grade students at SDN 36 Gunung Sarik, Padang City, and a pre-test and post-test test of effectveness by 26 students at SDN 36. Mount Sarik, Padang City. The results showed that the Module produced was categorized as very valid by the validator with an average value (3.61) both from the aspect of material feasibility (3.71), design aspect (3.8), and language aspect (3.33). The resulting Modules are categorized as very practical by educators with an average percentage (92.08%). And categorized as very practical by students with an average percentage (96.39%). And the results of the study on the effectveness test were categorized as high with a percentage (0.71). From the results of the study, it was concluded that the development of a scientific-based science learning Module for class V SDN 36 Gunung Sarik Padang City was valid, practical, and effectve so that it could be used in the learning process in class V SD (Elementary School).